ЧЎЛПОН ҲИКОЯЛАРИДА МИЛЛИЙЛИК (Scientific journal of the Fergana State University, 2023)
In this article the particular style of Chulpan in creating national images and characters was highlightened with the examples of story analysises. It was mentioned The great competence of the writer in using literary elements was widely opened